2016
DOI: 10.3892/or.2016.4767
|View full text |Cite
|
Sign up to set email alerts
|

miR-136 suppresses tumor invasion and metastasis by targeting RASAL2 in triple-negative breast cancer

Abstract: MicroRNAs play an important role in the regulation of cancer migration, invasion and metastasis. Patients with triple-negative breast cancer (TNBC) have a high incidence of early relapse and metastasis; however, the molecular basis for metastasis and recurrence in these individuals remains largely unknown. Herein, we demonstrate that miR-136 is an anti-invasive microRNA in TNBC and suppresses mesenchymal invasion and metastasis. Our results demonstrated that miR-136 was downregulated in TNBC and negative corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 32 publications
5
68
0
Order By: Relevance
“…Generally, it has been demonstrated that miR-136 was down-regulated in TNBC [35], which is consistent with our study. Yan et al showed that suppression of tumor invasion and metastasis by miR-136 was mediated through targeting RASAL2, which plays oncogenic role in TNBC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Generally, it has been demonstrated that miR-136 was down-regulated in TNBC [35], which is consistent with our study. Yan et al showed that suppression of tumor invasion and metastasis by miR-136 was mediated through targeting RASAL2, which plays oncogenic role in TNBC.…”
Section: Discussionsupporting
confidence: 82%
“…Yan et al showed that suppression of tumor invasion and metastasis by miR-136 was mediated through targeting RASAL2, which plays oncogenic role in TNBC. Moreover, expression of miR-136 was negatively correlated with WHO grades in TNBC [35]. In summary, the present study confirms the aberrant expression of miRNAs in TNBC patients when compared to healthy tissues.…”
Section: Discussionsupporting
confidence: 74%
“…miR-136-5p was also reported to be downregulated in triple-negative breast cancer by targeting RAS protein activator like 2, and act as a tumor suppressor (12). Yang et al (20) also described miR-136-5p as a tumor suppressor in lung adenocarcinoma, and revealed that this occurred through the targeting of SMAD family member (Smad)2 and Smad3.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-136-5p is involved in a number of types of carcinoma, including (12) and non-small cell lung cancer (NSCLC) (13). However, the function of miR-136-5p in RCC remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the abnormal expression of miR-136 has important roles in the progression of several types of human cancer (19)(20)(21)(22). To the best of our knowledge, the expression pattern, precise function and underlying molecular mechanisms of miR-136 have not been resolved in gastric cancer thus far.…”
Section: Introductionmentioning
confidence: 93%